Press Enter

Share with your friends and help them crack UPSC!

Or Share on

Answer

Correct Option is 11

Solution:Using step 1 in first row 11-6=5
First row becomes = 5 X
Similarly using step 4 in second row 16-2=14
Second row becomes= 14 2
Now, applying step 5 the resultant of second row becomes= 14+2= 16
As it is given that the resultant of second row is the value of X so value of X= 16
So, first row becomes after knowing the value of X= 5 16
Now, applying step 4 the resultant of first row becomes= 16-5= 11

Get access to all of our verified questions